Characterisation of scavenger receptor class B type 1 in rare minnow (Gobiocypris rarus). Issue 89 (June 2019) - Ou, Mi; Huang, Rong; Luo, Qing; Xiong, Lv; Chen, Kunci; Wang, Yaping
Abstract: Scavenger receptor class B type 1 (SRB1) is a transmembrane protein belonging to the scavenger receptors (SRs) family and it plays an important role in viral entry. Not much is known on SRB1 in teleost fish. Grass carp reovirus (GCRV) cause huge economic losses in grass carp industry. In this study, rare minnow ( Gobiocypris rarus ) was used as a model fish to investigate the mechanism of GCRV infection, which is sensitive to GCRV. The structure of SRB1 gene in G. rarus ( GrSRB1 ) was cloned and elucidated. GrSRB1 is composed of 13 exons and 12 introns, and its full-length cDNA is 2296 bp in length, with 1521 bp open reading frame (ORF) that encodes a 506 amino acid protein. The Gr SRB1 protein is predicted to contain a typical CD36 domain and two transmembrane regions. In G. rarus, GrSRB1 is expressed strongly in the liver (L), intestines (I), brain (B) and muscle (M), while it is expressed poorly in the heart (H), middle kidney (MK), head kidney (HK) and gills (G). After infection with GCRV, GrSRB1 expression was up-regulated in main immune tissues during the early infection period. Moreover, co-immunoprecipitation assays revealed that Gr SRB1 could interact with the outer capsid protein of GCRV (VP5 and VP7). These results suggest that Gr SRB1 could be a receptor for GCRV. We have managed to characterize the GrSRB1 gene and provide evidence for its potential functions for GCRV entry into host cells. Highlights: SRB1 gene in Gobiocypris rarus ( GrSRB1 ) was cloned and elucidated. GrSRB1 expression was up-regulated in main immune tissues after GCRV challenge. Gr SRB1 could interacted with the outer capsid protein of GCRV (VP5 and VP7). Gr SRB1 might play important role in GCRV entry into host cells.